2011
DOI: 10.1111/j.1365-2958.2011.07660.x
|View full text |Cite
|
Sign up to set email alerts
|

A central metabolic circuit controlled by QseC in pathogenic Escherichia coli

Abstract: Summary The QseC sensor kinase regulates virulence in multiple gram-negative pathogens, by controlling the activity of the QseB response regulator. We have previously shown that qseC deletion interferes with dephosphorylation of QseB thus unleashing what appears to be an uncontrolled positive feedback loop stimulating increased QseB levels. Deletion of QseC downregulates virulence gene expression and attenuates enterohemorrhagic and uropathogenic Escherichia coli (EHEC and UPEC), Salmonella typhimurium, and Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
156
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 113 publications
(167 citation statements)
references
References 59 publications
11
156
0
Order By: Relevance
“…2B). These observations confirm that QseC mediates NE's effects on LF82 flagellar expression and motility, with the caveat that NE-induced QseC-signaling has broad effects on bacterial physiology (19).…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…2B). These observations confirm that QseC mediates NE's effects on LF82 flagellar expression and motility, with the caveat that NE-induced QseC-signaling has broad effects on bacterial physiology (19).…”
Section: Resultssupporting
confidence: 71%
“…Previous gene expression analysis in WT vs. ΔqseC uropathogenic E. coli strains revealed that qseC deletion results in altered nucleotide, amino acid, and carbon metabolism (19). Observing that LF82 is more adept at persisting in a low-complexity microbiota (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a single oral dose of LED209 afforded protection to mice that were preexposed to Francisella tularensis, another pathogen in which AI-3-based QS contributes to virulence (188). Unfortunately, although LED209 did not inhibit EHEC growth (188), a recent study found that deletion of qseC results in large metabolic changes in both F. tularensis and EHEC that consequently affect virulence factor production (227). Thus, QseC inhibition is likely both an antimicrobial and an anti-QS strategy.…”
Section: Inhibition Of Signal Detection Synthetic Signal Analogues Anmentioning
confidence: 99%
“…8 UPEC harbor numerous CUP pili systems, the differential expression of which is thought to facilitate colonization of different niches. [9][10][11][12][13] Type 1 pili mediate adherence largely via the FimH tip adhesin, which recognizes and binds mannosylated moieties on biotic and abiotic surfaces. 4,6,[14][15][16][17][18][19][20] Within the host, FimH mediates UPEC binding to the bladder epithelium and is also required for proper formation of biofilm-like intracellular bacterial communities (IBCs) within bladder epithelial cells.…”
mentioning
confidence: 99%